Concentration-directed morphological evolution of boronate ester-based dynamic covalent nanoparticles: a facile approach for size and shape control. Issue 7 (23rd January 2018) - Zhao, Fuli; Dong, Anjie; Ma, Jinfeng; Deng, Liandong; Zhang, Jianhua
Abstract : Precursor concentrations dictated the formation processes of dynamic boronate nanoparticles, thus providing a facile route for morphological and size manipulation. Abstract : The birth-to-maturity trace of boronate nanoparticle formation derived from a couple of novel precursor monomers under homogeneous and mild conditions demonstrated a concentration-dependent nucleation and growth process and thus provided a facile approach for manipulation of their size and shape.